2018
DOI: 10.1186/s41687-018-0049-2
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of the Ulcerative Colitis patient-reported outcomes signs and symptoms (UC-pro/SS) diary

Abstract: BackgroundThe clinical course of ulcerative colitis (UC) and the effects of treatment are assessed through patient-reported signs and symptoms (S&S), and endoscopic evidence of inflammation. The Ulcerative Colitis Patient-Reported Outcomes Signs and Symptoms (UC-PRO/SS) measure was developed to standardize the quantification of gastrointestinal S&S of UC in clinical trials through direct report from patient ratings.DesignThe UC-PRO/SS was developed by collecting data from concept elicitation (focus groups, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 18 publications
0
40
0
Order By: Relevance
“…While at least one other inflammatory bowel disease PRO initiative has cited the FDA guidance, endoscopy was not incorporated in the development of the CD‐PRO/SS and UC‐PRO/SS measures 7,8 . Participants in the CD‐PRO/SS development study were enrolled based on physician‐confirmed biopsy and clinical disease activity was assessed using the Sandler estimated Crohn's Disease Activity Index (SeCDAI), without endoscopy 7,26 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While at least one other inflammatory bowel disease PRO initiative has cited the FDA guidance, endoscopy was not incorporated in the development of the CD‐PRO/SS and UC‐PRO/SS measures 7,8 . Participants in the CD‐PRO/SS development study were enrolled based on physician‐confirmed biopsy and clinical disease activity was assessed using the Sandler estimated Crohn's Disease Activity Index (SeCDAI), without endoscopy 7,26 .…”
Section: Discussionmentioning
confidence: 99%
“…Guidance documents issued by the European Medicines Agency (EMA) and US Food and Drug Administration (FDA) indicate that a co‐primary endpoint consisting of a PRO measure and an endoscopic outcome is required in future inflammatory bowel disease registration trials 5,6 . While the Crohn's Disease Patient‐Reported Outcomes Signs and Symptoms (CD‐PRO/SS) diary 7 and Ulcerative Colitis Patient‐Reported Outcomes Signs and Symptoms (UC‐PRO/SS) diary 8 were established according to the FDA‐endorsed pathway, endoscopic disease activity was not evaluated in the development studies. This represents an important potential shortcoming given that objective measures of inflammatory bowel disease activity do not necessarily correspond to symptom‐based assessments.…”
Section: Introductionmentioning
confidence: 99%
“…In alignment with the focus on PROs by health authorities, Roche and Genentech, in cooperation with a small consortium, have worked to develop the UC-PRO and CD-PRO [18,19]. The UC-PRO and CD-PRO are modular instruments that were designed to comprehensively assess the signs, symptoms, and impact of UC and Crohn's disease, capturing the experience from the perspective of the patient.…”
Section: What Is the Optimal Methods To Assess Disease Activity And DImentioning
confidence: 99%
“…PROs, including the Inflammatory Bowel Disease Questionnaire, EuroQoL-5D, UC-PRO tool (“signs and symptoms” and “systemic systems” modules), Crohn’s disease (CD)-PRO tool (“signs and symptoms” and “systemic systems” modules), components of CDAI (SF, AP, general well-being) and components of MCS [SF and rectal bleeding score (RB)], are collected daily using electronic PRO devices. The etrolizumab program uses the UC-PRO Signs and Symptoms (SS) and CD-PRO/SS, the first PRO tools to undergo a rigorous development process outlined by the FDA, with input from patients and clinical experts [ 18 , 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…Since the STRIDE recommendations, newer PRO tools, including more clinical variables (abdominal pain and urgency for UC) in accordance with FDA guidance, have been developed, however their applicability in clinical trial design or everyday clinical practice still remain to be validated[34-36]. Various other PROs have already been used in clinical trials reporting depression, anxiety, disability and other quality of life parameters, however available data on these PROs in IBD are yet limited.…”
Section: Instruments Of Tight Control In Disease Monitoringmentioning
confidence: 99%